Sustainability and the tourism and hospitality workforce: a thematic analysis - Baum, Tom; Cheung, Catherine; Kong, Haiyan; Kralj, Anna; Mooney, Shelagh; Thanh, Hải Nguyễn Thị; Ramachandran, Sridar; Ružić, Marinela Dropulić; Siow, May Ling (M D P I AG, 2016)
This paper is about the position of workforce and employment considerations within the sustainable tourism narrative. The paper aims to address the relative neglect of this area within the discourse of sustainable tourism and highlights references to the workforce within the United Nations’ 2030 Agenda for Sustainable Development. The discussion follows the emerging field of sustainable human resource management and the contribution that this can make to meeting both the UN Sustainable Development Goals and to enhancing the recognition of workforce and employment issues within the related debate in tourism. The body of the paper highlights examples of key dimensions of work and employment across varied tourism contexts, where sustainability is of increasing consequence and significance. The paper concludes by drawing together the implications of these “mini-cases” and locating them within key principles of the 2030 Agenda for Sustainable Development.